2021
DOI: 10.3390/nano11102674
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fabrication of Flexible, Thermochromic Vanadium Dioxide Films for Smart Windows

Abstract: Monoclinic-phase VO2 (VO2(M)) has been extensively studied for use in energy-saving smart windows owing to its reversible insulator–metal transition property. At the critical temperature (Tc = 68 °C), the insulating VO2(M) (space group P21/c) is transformed into metallic rutile VO2 (VO2(R) space group P42/mnm). VO2(M) exhibits high transmittance in the near-infrared (NIR) wavelength; however, the NIR transmittance decreases significantly after phase transition into VO2(R) at a higher Tc, which obstructs the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 149 publications
0
20
0
Order By: Relevance
“…The transmitted NIR light increases room temperature, leading to excessive use of air conditioning for temperature regulation . Hence, the reduction of energy consumption requires the application of energy-saving windows which should have excellent NIR-shielding ability, while keeping their high visible light transmission property …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmitted NIR light increases room temperature, leading to excessive use of air conditioning for temperature regulation . Hence, the reduction of energy consumption requires the application of energy-saving windows which should have excellent NIR-shielding ability, while keeping their high visible light transmission property …”
Section: Introductionmentioning
confidence: 99%
“…5 Hence, the reduction of energy consumption requires the application of energysaving windows which should have excellent NIR-shielding ability, while keeping their high visible light transmission property. 6 Traditional bulk-tinted float glass doped with colorant ions (e.g., Co 2+ ) is a type of NIR-shielding glass. 7 Although tinted glasses absorb NIR light, their visible transmittance is very low, and hence their application for room windows is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the technological advancement, it is possible to produce a smooth and uniform surface for the VO 2 films. For instance, RF magnetron sputtering, van der Waal Epitaxy and chamber-based depositions are among the interesting techniques that were used to growth flexible and uniform VO 2 layers for various applications [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The transition temperature setting of vanadium dioxide is usually controlled via impurity doping with lower- and higher-valence transition metals, such as W, Nb, Cr, Mo, and Ti. However, to obtain highly effective thermochromic and electrochromic properties, a thin film of pure-phase VO 2 is required. For this purpose, various synthesis methods, such as strain-induced single-crystal substrates with the most preferred orientation, buffer layers, narrow oxygen partial pressures, and optimal growth temperatures, have already been studied. More recently, VO 2 has been adopted as a next-generation material with dynamic color adjustment for reflectors or transmitters because of its significantly low phase change, low power consumption, low toxicity, low-effort manufacture, wide range of fabrication techniques, stability, and reversible electrically and optically activated tuning. In particular, changes in optical properties, if induced in the visible spectral range, offer considerable benefits and ease of detection. Recently, photonic materials that are color-tunable in the visible spectral range, making them extremely attractive for application in temperature indicators, displays, memory, and other switchable optoelectronic devices, have been developed. For example, Song et al reported, based on their modeling results, that vanadium dioxide-based metamaterial absorbers for active color rendering and multiband photodetection can be realized .…”
Section: Introductionmentioning
confidence: 99%